Comparison of burnout, vigor and education satisfaction of music and art majors in department of fine arts education - Rasim Erol Demirbatır (International Journal of Evaluation and Research in Education (IJERE), 2020)
The success of an educational institution is largely based on student motivation and educational satisfaction and their happiness at their place of education. It is therefore very important to maintain high quality in education to determine the case of students' well-being in order to improve the standards of study. In this regard, the aim of this study was to identify the status of students in terms of their level of burnout, vigor and educational satisfaction at the Department of Fine Arts Education. There were 250 students participated in the study. To determine the level of burnout and vigor, Shirom Melamed Burnout and Vigor Measures were employed, and to measure the educational satisfaction levels, educational satisfaction questionnaire was used. The results show that music majors have lower vigor than art majors. Gender does not have significant effect on any of the scores. Burnout, vigor and educational satisfaction differ according to the year of education for music major, but only vigor differs for art majors. Mother’s education level has significant effect on burnout and vigor for music majors and on education satisfaction for art majors. GPA is not correlated with none of burnout, vigor or educational satisfaction.